Psychanthus (K. Schum.) Ridley (Zingiberaceae): Its Acceptance at Generic Level - Smith, R. M. (Edinburgh Journal of Botany, 2010)
Twenty-two species of Alpinia hitherto placed in sections Psychanthus and Pleuranthodium are transferred to the genus Psychanthus Ridley. The justification for the acceptance of Psychanthus, which is based on the cup-shaped character of the labellum is discussed, and the necessary new combinations made.